ANTDIABETIC ACTIVITY OF BARK EXTRACTS OF PTEROCARPUS SANTALINUS L. IN STREPTOZOTOCIN INDUCED DIABETIC RATS - D. PEER BASHA; * B. BHANU TEJA; M. SUBBARAO (The Bioscan, 2010)
After induction of diabetes aqueous extract of aquous extract of bark of Pterocarpus santalinus has been given to the treated rats to establish the protective role. Different doses Pterocarpus santalinus were evaluated for hypoglycemic activity in normal and streptozocin diabetic rats. The oral administration of aquoues extract at a dosage of 0.7 g/kg body weight exhibited a significant antidiabetic activity in STZ diabetic rats, whereas in normal rats no hypoglycemic activity was observed.